Compassion Fatigue and Mindfulness: Comparing Mental Health Professionals and MSW Student Interns. Issue 3 (4th May 2017) - Brown, Jodi L. Constantine; Ong, Jacqueline; Mathers, Jessica M.; Decker, James T.
ABSTRACT: The relationship between compassion fatigue and mindfulness in mental health professionals compared to Master of Social Work (MSW) students is explored. A convenience sample of mental health professionals ( n = 40) and MSW students ( n = 111) completed the Five Facet Mindfulness Questionnaire and Professional Quality of Life Scale. Results indicate a medium, negative correlation between compassion fatigue and mindfulness, with high levels of compassion fatigue associated with lower levels of mindfulness. There was no statistically significant difference between mental health workers and MSW students on the combined dependent variables. Results suggest that mindfulness protects against compassion fatigue regardless of professional or student status.